2021
DOI: 10.1093/ijpp/riab046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy services provided in public sector hospitals in Nigeria: a national survey

Abstract: Objectives Studies show that clinical pharmacy services are effective in optimizing medicines use and patients' outcomes. This study aimed to determine the clinical pharmacy services provided in public sector hospitals in Nigeria. Methods This was an online survey of 296 primary, secondary and tertiary care hospitals sampled purposively across the 36 States and Federal Capital Territory in Nigeria. Data analysis was conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Evidence gotten from countries such as South Africa indicated that pharmacist-led care interventions were highly effective in long-term disease prevention, medication therapy management, and improvement in drug-related patient outcomes. [31][32][33] There were also lower potentials for medication errors and non-adherence to long term disease therapies when pharmaceutical care services were provided by pharmacists which further emphasize the roles pharmacist play in strengthening a nation's health care system. 31,34,35 Pharmacists would continue to play an important role in strengthening the health care system.…”
Section: Integral Roles That Pharmacists Play In Strengthening the He...mentioning
confidence: 99%
“…Evidence gotten from countries such as South Africa indicated that pharmacist-led care interventions were highly effective in long-term disease prevention, medication therapy management, and improvement in drug-related patient outcomes. [31][32][33] There were also lower potentials for medication errors and non-adherence to long term disease therapies when pharmaceutical care services were provided by pharmacists which further emphasize the roles pharmacist play in strengthening a nation's health care system. 31,34,35 Pharmacists would continue to play an important role in strengthening the health care system.…”
Section: Integral Roles That Pharmacists Play In Strengthening the He...mentioning
confidence: 99%
“…Typically, CPs and hospitals work in isolation, and this disconnect extends to the relationship between the practitioners in these two facilities, thereby negatively affecting collaboration and smooth TOC 16 . Anecdotal evidence suggests that many private hospitals in Nigeria lack significant pharmacist engagement in their operations 23 . Similarly, some community pharmacists have been implicated in overreaching practices, such as offering prescription‐only medications to patients without a physician's input 24 .…”
Section: Barriers Hindering Effective Referral/care Transition Proces...mentioning
confidence: 99%
“…16 Anecdotal evidence suggests that many private hospitals in Nigeria lack significant pharmacist engagement in their operations. 23 Similarly, some community pharmacists have been implicated in overreaching practices, such as offering prescription‐only medications to patients without a physician's input. 24 As such, professional silos created by a lack of trust and unhealthy competitive behaviors between care providers may deny patients quality care, where one provider hesitates to refer when due or does so as a mere “handover” devoid of feedback, follow‐up or consideration of patients' needs.…”
Section: Barriers Hindering Effective Referral/care Transition Proces...mentioning
confidence: 99%
“…[20][21][22] Low availability of mental health experts and poor involvement of pharmacists in clinical care of patients is also a notable challenge in Nigeria. 17,23 Poor institutionalization of collaborative care with pharmacists in Nigerian hospitals is a significant barrier to healthcare delivery in the country. 24 These situations reduce access to optimal mental healthcare, and prevents the utilization of the pharmacists' clinical skills thereby interfering with potential benefits for the patients.…”
Section: Introductionmentioning
confidence: 99%